ON THE ROLE OF KI-67 AND P53 PROLIFERATION MARKERS IN PATIENTS WITH RECURRENT MACRO AND GIANT INACTIVE PITUITARY TUMORS (American Journal of Technology and Applied Sciences, 2024)
The aim of the study was to study the prognostic value of the proliferation markers Ki-67 and p53 in patients with recurrent macro and giant inactive pituitary adenomas.